Contribution of Agility And Speed to Ball Drifting Skills in Students Football Extracurricular - Sumaryadi Sumaryadi (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The purpose of this study was to determine the contribution of agility and speed towards dribbling skills students of football extracurricular. Methodology: This type of research is correlation. The population in this study were students of soccer extracurricular Public High School 5 Bandar Lampung, amounting to 20 people. The sampling technique used was total sampling so that the number of samples in this study were 20 students. The test instrument used was the shuttle run test, 30 meter run test and dribbling test. The data analysis technique used is the r test. Main Findings: Based on the results of the calculation, it can be seen that the value of the contribution of agility and speed to the results of dribbling the ball of football extracurricular students Public High School 5 Bandar Lampung is = 44.76% Novelty/Originality of this study: This research presents novelty by integrating in-depth empirical analysis regarding the contribution of agility and speed to ball dribbling skills in students who take part in extracurricular football. This study uses a quantitative approach that specifically measures how these two physical components individually and synergistically influence dribbling ability, which is a crucial skill in soccer.